如图, 在边长为 3 的正方形 $A B C D$ 中, 点 $E$ 是边 $A B$ 上的点, 且 $B E=2 A E$, 过点 $E$ 作 $\mathrm{DE}$ 的垂线交正方形外角 $\angle \mathrm{CBG}$ 的平分线于点 $\mathrm{F}$, 交边 $\mathrm{BC}$ 于点 $\mathrm{M}$, 连接 $\mathrm{DF}$ 交边 $\mathrm{BC}$ 于 点 $N$, 则 $M N$ 的长为
$ \text{A.} $ $\frac{2}{3}$ $ \text{B.} $ $\frac{5}{6}$ $ \text{C.} $ $\frac{6}{7}$ $ \text{D.} $ $1$
【答案】 B

【解析】

$$
\begin{aligned}
& \because \mathrm{BE}=2 \mathrm{AE}, \mathrm{AB}=3, \therefore \mathrm{AE}=1, \mathrm{BE}=2, \\
& \because \mathrm{DE} \perp \mathrm{EF}, \therefore \angle \mathrm{FEG}+\angle \mathrm{DEA}=90^{\circ} \text {, 又 } \because \angle \mathrm{DEA}+\angle \mathrm{EDA}=90^{\circ}, \therefore \angle \mathrm{FEG}=\angle \mathrm{EDA} \text {, } \\
& \text { 又 } \because \angle \mathrm{MBE}=\angle \mathrm{EAD}=90^{\circ}, \therefore \triangle \mathrm{MBE} \sim \triangle \mathrm{EAD}, \therefore \frac{\mathrm{BE}}{\mathrm{AD}}-\frac{\mathrm{BM}}{\mathrm{AE}}, \quad \text { 即 } \frac{2}{3}-\frac{\mathrm{BM}}{1}, \therefore \mathrm{BM}=\frac{2}{3}
\end{aligned}
$$
过 $\mathrm{F}$ 作 $\mathrm{FG} \perp \mathrm{AG}$ 于 $\mathrm{G}, \mathrm{FH} \perp \mathrm{BC}$ 于 $\mathrm{M}$, 令 $\mathrm{BG}=\mathrm{t}, \because \mathrm{BF}$ 为 $\angle \mathrm{CBG}$ 角平分线, $\therefore \mathrm{FH}=\mathrm{FG}, \therefore$ 四边形 $\mathrm{HFGB}$ 为正方形, $\therefore \mathrm{FG}=\mathrm{FH}=\mathrm{BG}=\mathrm{t}, \because \mathrm{FG} / / \mathrm{MB}, \therefore \triangle \mathrm{EBM} \sim \triangle \mathrm{EGF}, \therefore \frac{\mathrm{BM}}{\mathrm{FG}}=\frac{\mathrm{BE}}{\mathrm{GE}}$, 即 $\frac{\frac{2}{3}}{\mathrm{t}}=\frac{2}{2+\mathrm{t}}$, 解得 $\mathrm{t}=1, \therefore \mathrm{CH}=\mathrm{BC}-\mathrm{BH}=3-1=2, \because \mathrm{FH} / / \mathrm{BG} / / \mathrm{CD}, \therefore \triangle \mathrm{CDN} \sim \triangle \mathrm{HFN}, \therefore \frac{\mathrm{FH}}{\mathrm{CD}}=\frac{\mathrm{HN}}{\mathrm{CN}}$, 即 $\frac{1}{3}-\frac{\mathrm{HN}}{\mathrm{CN}}, \mathrm{CN}=3 \mathrm{HN}, \therefore \mathrm{CN}=\frac{3}{4} \mathrm{CH}=\frac{3}{2}$, 故 $\mathrm{MN}=\mathrm{BC}-\mathrm{BM}-\mathrm{CN}=3-\frac{2}{3}-\frac{3}{2}-\frac{5}{6}$, 故选 B.
系统推荐